Sans mari, sans travail, sans morale ? Aider et contrôler les « chômeuses seules » (Suisse, années 1930) - Carola Togni (Genre & Histoire)
The crisis of the 1930s constituted a key moment in the definition of the modern concept of Unemployment when the criteria of sex and marital status became critical. In several countries unemployed married women were partially or totally excluded from aid as they were considered dependents of their husbands; the situation was different for single, widowed or divorced woman. Authorities granted these women state aid and encouraged them to seek paid work. This article analyses the control exerted over "unemployed women without husbands," specifically with regard to their morals and sexuality. It shows how the policies with respect to these unemployed women contributed to a sexual management of the labor market, while promoting the gender norms of the traditional family.